1996
DOI: 10.1016/s0006-3495(96)79512-7
|View full text |Cite
|
Sign up to set email alerts
|

IR spectroscopic study of the structure and phase behavior of long-chain diacylphosphatidylcholines in the gel state

Abstract: Fully hydrated dispersions of simple linear saturated diacylphosphatidylcholines with even-numbered acyl chains of lengths from 18 to 24 carbons can exist in a low-temperature, highly ordered, orthorhombic phase (G(o)) that differs from the L beta phase (Gd) normally found for shorter chains. The temperature behavior of these dispersions has been studied by infrared spectroscopy. Chain packing in the G(o) phase was found to be nearly identical to that of the orthorhombic phase of crystalline n-alkanes. With in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 7 publications
4
75
0
Order By: Relevance
“…This is confirmed by The rest of the members of the series are amorphous at room temperature (Davison and Corish, 1955;Snyder et al, 1996) and DSC thermograms display clear vitreous transitions with Tg values generally increasing with the hydroxylation degree of the monomer ( Table 2).…”
Section: Dbsa Poly Trihpamentioning
confidence: 58%
“…This is confirmed by The rest of the members of the series are amorphous at room temperature (Davison and Corish, 1955;Snyder et al, 1996) and DSC thermograms display clear vitreous transitions with Tg values generally increasing with the hydroxylation degree of the monomer ( Table 2).…”
Section: Dbsa Poly Trihpamentioning
confidence: 58%
“…), short-and long-chain lipids form phases of different packing at room temperature (i.e. hexagonal and orthorhombic, respectively) [75]. In vivo and in vitro studies of diseased and healthy SC have also demonstrated a direct correlation between the lipid chain length and the packing density and repeat distance in the resulting lipid phases; the relative content of the different ceramides classes also influences the molecular organization of the lipid lamellae [76][77][78][79][80].…”
Section: Formation Of the Lipid Lamellaementioning
confidence: 99%
“…were worked out over a period of 50 years through the seminal studies of alkanes and polyethylene from (amongst others) the laboratories of Snyder (Berkeley) [9][10][11][12][13], Zerbi (Milan) [14][15][16], and Shimanouchi (Tokyo) [17,18]. The original correlations have been extended to assemblies of lipids, lipid-protein complexes, and more recently tissues, including skin.…”
Section: Ir Spectra-structure Relationships For Chain Order and Packimentioning
confidence: 99%
“…13 Flowchart of the complex, overlapping temporal sequence of events that take place following an acute cutaneous wounding of human skin (adapted from Ref 41)…”
mentioning
confidence: 99%